Study on the effect of doping time of MEH-PPV:IMWNT nanocomposite for organic solar cell application: article - Shaari, Nor Azira Akma; Mohd Noor, Uzer (2013)
ln this paper, the properties of nanocomposited MEHPPV:I-MWNT thin film arc reported by varying the time of deposition of Iodine doped multiwall carbon nanotubes (l-MWNT) in CVD (Chemical Vapor Deposition) to 15. .10, 60,90 and 120 minutes. The l-MWNT is then mixed with MEH-PPV solution then being sonicated for 1 hour. The yielded MEH-PPV:I-MWNTT is being deposited on substrates by using spin coating technique, The characterization is to be done to investigate the optical, electrical and physical properties of the thin films.